CONSUMER INTENTION TOWARDS ONLINE SHOPPING IN MALAYSIA - Rashid Ating; Tan Shi Wen; NurulHuda Mohd Satar; Nur Annizah Ishak (International Journal of Accounting, Finance and Business, 2020)
There is a rapid expansion of online purchasing activities in Malaysia and a marked increase in government’s attention towards promoting the use of electronic transaction. However, the issue of privacy and security remain among the major concerns. This paper aims to examine the determinants of consumer’s intention to engage in online shopping in Malaysia. Utilising primary data collected from 392 respondents, we examined the determinants based on Theory of Planned Behaviour and Technological Acceptance Model using Structural Equation Modelling approach. We found that consumer’s intention to shop online in Malaysia is significantly influenced by consumer’s attitude toward online shopping and perceived behavioural control. Privacy remains a concern and privacy features of online transaction would boost consumer’s positive attitude towards online shopping.